2018
DOI: 10.1016/j.ijrobp.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hypothyroidism in Hodgkin Lymphoma Survivors After Intensity Modulated Versus 3-Dimensional Radiation Therapy

Abstract: The percentage of the thyroid receiving 25 Gy and the volume of the thyroid spared from 25 Gy predicted the risk of hypothyroidism after either IMRT or 3D-CRT for HL. IMRT may confer a higher risk than 3D-CRT unless a treatment avoidance structure is used during planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 23 publications
2
32
0
1
Order By: Relevance
“…For patients with lymphoma, much lower RT organ constraints are considered appropriate, as established by survivorship studies and/or dosimetric RT studies based on patient populations with lymphoma. [16][17][18][19][20]24 We compared the RT doses administered to the heart (Figure 1A), lung ( Figure 1B), breasts among the 18 female patients ( Figure 1C), thyroid gland ( Figure 1D), parotid glands ( Figure 1E), and submandibular glands ( Figure 1F) with the QUANTEC and lymphoma dose constraints. The mean heart mean dose was 0.8 Gy (range, 0-4.8 Gy) ( Figure 2); all patients were below both QUANTEC (26 Gy) and lymphoma (5 Gy) MHD constraints.…”
Section: Resultsmentioning
confidence: 99%
“…For patients with lymphoma, much lower RT organ constraints are considered appropriate, as established by survivorship studies and/or dosimetric RT studies based on patient populations with lymphoma. [16][17][18][19][20]24 We compared the RT doses administered to the heart (Figure 1A), lung ( Figure 1B), breasts among the 18 female patients ( Figure 1C), thyroid gland ( Figure 1D), parotid glands ( Figure 1E), and submandibular glands ( Figure 1F) with the QUANTEC and lymphoma dose constraints. The mean heart mean dose was 0.8 Gy (range, 0-4.8 Gy) ( Figure 2); all patients were below both QUANTEC (26 Gy) and lymphoma (5 Gy) MHD constraints.…”
Section: Resultsmentioning
confidence: 99%
“…Receiver operating characteristics ROC analysis (14,15), already adopted by other authors to identify dosimetric parameters associated with RT damage (16,17), was used to identify the dosimetric parameters related to the risk of G2 alopecia. The maximum value of the Youden index (J) (18) was used for selecting the optimal cut-off point for each dosimetric variable.…”
Section: Methodsmentioning
confidence: 99%
“…Data regarding volumes in cc were collected both for the whole scalp and for the areas of acute alopecia. The following dosimetric parameters were collected: dose received by 0.1 cc of the ROI (D 0.1cc ), mean dose (D mean ), absolute volumes that received 16,20,25,30,35,40, and 43 Gy (V 16Gy , V 20Gy , V 25Gy , V 30Gy , V 35Gy , V 40Gy , and V 43Gy ).…”
Section: Hair Loss Assessmentmentioning
confidence: 99%
“…The same study also identified a threshold value for V20: in patients with a V20 higher or lower than 82.4%, the risk of hypothyroidism was 60.7 and 13.6%, respectively. A more recent study [83] assessed the risk of hypothyroidism in patients treated with IMRT: for V25, the threshold value was 63.5% (37% vs. 80% hypothyroidism), while the cut-off for V30 was 62%. Another parameter found to be related to the risk of functional damage was the amount of thyroid tissue receiving less than 25Gy, with a threshold value at 2.2 ml.…”
Section: Thyroidmentioning
confidence: 99%